2017
DOI: 10.1080/14686996.2016.1278352
|View full text |Cite
|
Sign up to set email alerts
|

Formation of metal clusters in halloysite clay nanotubes

Abstract: We developed ceramic core-shell materials based on abundant halloysite clay nanotubes with enhanced heavy metal ions loading through Schiff base binding. These clay tubes are formed by rolling alumosilicate sheets and have diameter of c.50 nm, a lumen of 15 nm and length ~1 μm. This allowed for synthesis of metal nanoparticles at the selected position: (1) on the outer surface seeding 3–5 nm metal particles on the tubes; (2) inside the tube’s central lumen resulting in 10–12 nm diameter metal cores shelled wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
66
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 112 publications
(71 citation statements)
references
References 17 publications
5
66
0
Order By: Relevance
“…Combination of silver nanoparticles with DCOIT loaded into an antifouling coating show synergetic effects against fouling [30]. Naturally excavated cheap halloysite nanotubes can be used as a container for DCOIT antifouling agent and serve as a template for Ag-particles formation preventing their undesirable aggregation [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Combination of silver nanoparticles with DCOIT loaded into an antifouling coating show synergetic effects against fouling [30]. Naturally excavated cheap halloysite nanotubes can be used as a container for DCOIT antifouling agent and serve as a template for Ag-particles formation preventing their undesirable aggregation [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Addition of HNT into polymeric materials to improve the composite strength has been proposed . The applications of inexpensive HNT for water purification, as support for catalytic nanoparticles, and as nanoreactor or nanotemplate for material synthesis were also reported.…”
Section: Introductionmentioning
confidence: 99%
“…4). 66 In this way, it is also possible avoid metal aggregation. Ouyang et al reported the preparation of Ag NPs/HNTs composites under vacuum conditions.…”
mentioning
confidence: 99%